2013
DOI: 10.1051/epjconf/20135401016
|View full text |Cite
|
Sign up to set email alerts
|

Complex photonic structures for energy efficiency

Abstract: Summary. -Photonic structures are playing an increasingly important role in energy efficiency. In particular, they can help to control the flow of light and improve the optical properties of photovoltaic solar cells. We will explain the physics of light transport in such structures with a special focus on disordered materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This signal enhancement must be related to two different effects: light trapping within the pores and carrier confinement. The first effect causes absorption enhancement, which has already been reported for a two-dimensional random film of finite thickness, ,, but never reported until now for 3D systems. The second effect has already been observed in ordered germanium nanoporous materials, and in Ge nanowires, but never in nanoporous Ge films obtained by ion implantation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This signal enhancement must be related to two different effects: light trapping within the pores and carrier confinement. The first effect causes absorption enhancement, which has already been reported for a two-dimensional random film of finite thickness, ,, but never reported until now for 3D systems. The second effect has already been observed in ordered germanium nanoporous materials, and in Ge nanowires, but never in nanoporous Ge films obtained by ion implantation.…”
Section: Discussionmentioning
confidence: 72%
“…Interference could lead to weak or strong (Anderson) localization, where diffusion is decreased or completely halted. It has been demonstrated that a two-dimensional random film of finite thickness can lead to a large broad-band absorption enhancement, but no direct observation of this phenomena in a three-dimensional system has been reported until now. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation